Analisis Perubahan Garis Pantai pada Desa Liang serta Alternatif Penanggulanganya - Sutrahitu, Gilbert Wullur; Ayal, Mansye Ronal (Jurnal Ilmiah Rekayasa Sipil, 2023)
Liang Village Beach is an area located in the north of Ambon Island, with great marine tourism potential. However, the coastal part of this village experienced erosion marked by the resignation of the coastline and the erosion of agricultural land. This study aims to find out, analyze erosion and coastline changes using the CERC method. The variables observed are the distribution of sediment particles and the pattern of coastline changes, so that it can be estimated the area affected by sedimentation and erosion in the range of 1, 5, and 10 years in the future. The data used are data on the initial coastline, coastal slope, specific gravity of seawater (1.025 tons/m3.) and gravity of the earth (g) (9.81 m/s2). The wave data required in numerical calculations consist of the height of the rupture wave (Hb), the depth of the ruptured wave (db), the rapid propagation of the ruptured wave (Cb), and the angle of incidence of the ruptured wave ( ). Based on numerical calculations, the change in the coastline of 1 year, 5 years and 10 years is the retreat of the coastline (erosion) that occurred on the coast of Liang Village. The changes that occur are caused by waves that are more dominant for the northwest and north, causing erosion along the coast, therefore there is a need for alternative countermeasures such as Revetment to prevent further erosion and accretion on the coast of Liang Village.